Religious motifs in everyday practice and the value orientations of kazakh youth (The Journal of Psychology and Sociology, 2017)
This article discusses some issues of formation of value consciousness of Kazakh youth and religious values. The methodological basis of research value is the classification values through their separation on the basis of allocation of evaluation items – objects, which is attributed to the value, or objects whose values are compared. With this approach, isolated religious, ethical, aesthetic, economic, legal, political or other values. The object of research interest, there appear not only internal (complex in nature) the processes of formation and preservation of religion in the public and individual consciousness or the assessment of the role of religion as a social institution, and the practical problems of religious socialization of young people. Studies have shown that religious denominations make up only a small part of the socialization agents from the work which becomes religious socialization. Accordingly, the desired model of religious socialization can be represented by the following main components: personal, internal identity and its strengthening at the institutional level and the inclusion of social (ceremonial, religious) practices that characterize a particular religion. Values appear and function as human orientation and certain cultural preferences matrix. In addition, the values are historical, dynamic and pluralistic, in the study required to take into account that they are not mutually exclusive. For each representative of the youth target group is characterized by serial or parallel adoption of values on various axes, including criticism / recognition of traditional ethno-cultural and religious values; choice of life goals and values of work and education; orientation in the field of family values; awareness and enhancing legal values and civic participation and other purposes. The values of the religious consciousness of youth are considered in the context of the choice of the motives of social action, leisure practices, behavioral patterns. The basic methodological basis of research of values is their classification by the division on the basis of allocation of evaluation subjects – objects, to which the value is attributed, or objects whose values are mapped (what is valued?). Within this approach ethical, aesthetic, economic, legal, religious, political and other values are distinguished.Key words: youth, values, values, religion, identity and social consciousness.